Risk factors for cardiovascular diseases and coronary artery disease among military population - A. E. Masimova; M. N. Mamedov (Кардиоваскулярная терапия и профилактика, 2021)
The review analyzes the features of coronary artery disease (CAD) and risk factors (RFs) of cardiovascular diseases (CVDs) in military population. Despite the urgency of the problem in recent years, there are only few publications on this topic. This paper presented data of international and Russian studies of CVDs and related RFs among various military personnel and war veterans, taking into account the age and social characteristics of the groups. There is a tendency towards an increase in CVD prevalence, which is due not only to age, but also to multiple RFs. Along with conventional RFs, the specifics of military service in general, special situation, active restructuring of activity areas, increased stress, intensive physical and professional training are specific cardiovascular risk factors and affect the risk of CAD. Regular medical examinations with primary and secondary prevention with correction of biological, behavioral and social factors can reduce the rate of CAD among military population.